Development of Concept Mastery Instruments Based on Scientific Literacy in Chemistry Subjects - Zulkhairi, M.Pd - (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The research "Development of Science Literacy-Based Concept Mastery Instruments in Chemistry Subjects in Class XI Even Semester" was conducted to: (1) develop scientific literacy-based concept mastery instruments, (2) find out student learning outcomes, and (3) find out teacher responses to mastery instruments developed scientific literacy-based concepts. The research method used is Research and Development (R&D) with a 4D development design consisting of Define, Design, Develop and Disseminate. The research subjects consisted of four chemistry teachers consisting of one MAN Model Banda Aceh teacher, one MAN 2 Banda Aceh teacher, one Inshafuddin High School teacher, and one SMAN 5 Banda Aceh teacher. The trials were limited to the cognitive instruments developed and applied to one class XI from each school. The instruments used were interview guide sheets, teacher needs analysis questionnaires, and multiple choice test questions based on scientific literacy. The results showed that scientific literacy-based concept mastery instruments were declared valid and suitable for use in limited trials with an average validator result of 98.70%. The achievement of the trial results was limited to students from four SMA/MAN in Banda Aceh City amounting to 84.25%, so that the developed scientific literacy-based concept mastery instrument was able to improve student learning outcomes. The teacher gave a positive response to the scientific literacy-based concept mastery instrument which was developed in the very good category